Compact Unequal Power Divider with Filtering Response - Wei-Qiang Pan; Jin-Xu Xu; Kai Xu Wang; Xiao Lan Zhao (International Journal of Antennas and Propagation)
We present a novel unequal power divider with bandpass responses. The proposed power divider consists of five resonators and a resistor. The power division ratio is controlled by altering the coupling strength among the resonators. The output ports have the characteristic impedance of 50 Ω and impedance transformers in classical Wilkinson power dividers are not required in this design. Use of resonators enables the filtering function of the power divider. Two transmission zeros are generated near the passband edges, resulting in quasielliptic bandpass responses. For validation, a 2 : 1 filtering power divider is implemented. The fabricated circuit size is 0.22 λg × 0.08 λg, featuring compact size for unequal filtering power dividers, which is suitable for the feeding networks of antenna arrays.